2010
DOI: 10.1021/es903383a
|View full text |Cite
|
Sign up to set email alerts
|

Identifying New Persistent and Bioaccumulative Organics Among Chemicals in Commerce

Abstract: The goal of this study was to identify commercial chemicals that might be persistent and bioaccumulative (P&B) and that were not being considered in current Great Lakes, North American, and Arctic contaminant measurement programs. We combined the Canadian Domestic Substance List (DSL), a list of 3059 substances of "unknown or variable composition complex reaction products and biological materials" (UVCBs), and the U.S. Environmental Protection Agency (U.S. EPA) Toxic Substances Control Act (TSCA) Inventory Upd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
349
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 386 publications
(360 citation statements)
references
References 37 publications
11
349
0
Order By: Relevance
“…8,13,30,31 Generally, a compound with log K ow > 5 is considered to be potentially bioaccumulative. 8,13,35,36 Although the log K ow values of the monomodified byproducts were lower than the corresponding derivatives, they all showed log K ow > 5, indicating their potential bioaccumulative abilities. 8 For TBBPA, TBBPS and the byproducts, the log K ow ranged from 5.21 to 9.36 15 and no significant relationship was observed between log K ow values and TMFs.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…8,13,30,31 Generally, a compound with log K ow > 5 is considered to be potentially bioaccumulative. 8,13,35,36 Although the log K ow values of the monomodified byproducts were lower than the corresponding derivatives, they all showed log K ow > 5, indicating their potential bioaccumulative abilities. 8 For TBBPA, TBBPS and the byproducts, the log K ow ranged from 5.21 to 9.36 15 and no significant relationship was observed between log K ow values and TMFs.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…16−18,39−42 Currently, TBBPA-MAE and TBBPA-MDBPE have been identified as degradation products of TBBPA-BAE and TBBPA-BDBPE according to the results of UM-PPS (http://umbbd.msi.umn.edu/predict/). 8,14 TBBPA-MAE, TBBPA-MDBPE, and TBBPS-MDBPE can be generated as the degradation products through the cleavage of a single ether bond in TBBPA-BAE, TBBPA-BDBPE, and TBBPS-BDBPE, respectively. 13−15 TBBPA and TBBPS are common degradation products that occur with the cleavage of two ether bonds in TBBPA and TBBPS derivatives.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…2 The commercial product Firemaster 550 which is a mixture of 2-ethylhexyl 2,3,4,5-tetrabromobenzoate (TBB) and bis(2-ethylhexyl)-tetrabromophthalate (TBPH) in a ratio of 4:1, 1,2-bis(trbromophenoxy)-ethane (BTBPE) and 1,2-bis(2,3,4,5,6-pentabromophenyl)ethane (DBDPE) have been produced as the replacements of PBDE technical mixtures penta-BDE, octa-BDE, and deca-BDE, respectively. The global market demand for these emerging chemicals has rapidly increased in recent years, 2,3 resulting in the widespread occurrence of AHFR residues in sediment, 4 air, 5,6 sludge, 7 and organisms. 8,9 The economic development patterns in China have continuously evolved in recent decades.…”
Section: ■ Introductionmentioning
confidence: 99%
“…7 Its high calculated octanol−water partition coefficient (log K ow = 7.37) and bioconcentration factor (log BCF = 4.30) indicate that TBC is bioaccumulative. 10 The long-range transport potential of TBC is unknown, but the estimated low vapor pressure (1.57 × 10 −13 Pa) and high octanol−air partition coefficient (log K oa = 23.7) suggest it is strongly sorptive to surfaces and particles. Recent studies on zebrafish embryos suggested that exposure to TBC causes a variety of potential reproductive and endocrine disrupting toxic effects, damaging mitochondria and causing defects in gas bladder inflation.…”
Section: ■ Introductionmentioning
confidence: 99%